Prevalence and risk indicators of tooth wear in 17 year old school children in Colombo District in Sri Lanka - Ratnayake, N.C (My University, 2008)
A cross sectional school based study was conducted in order to determine prevalence, severity, distribution and risk indicators of and awarencess about tooth wear among the adolescents. A total of 1200 17 year olds were selected from the schools in the Colombo district using a two stage cluster sampling method combined with probability proportional to size ( PPS) Technique. Subjects were requested to complete a self-administered questionnaire on potential risk indicators and knowledge about tooth wear. Oral examination was carried out to assess tooth wear using Smith and Knight ( 1984a). Tooth wear index. In the second component of the study, seventeen brands of carbonated beverages avilable in the market were analysed for acidity, calcium and fluoride ion concentrations. Prevalence of tooth war was 22 percent. Fourteen -per-cent only had tooth wear lesions confined to the enamel while 9 percent had tooth wear lesions extending up to the dentine. The mean number of tooth surfaces affected by tooth wear per subject was 3.5 while it was 2.6 and 1.0 for enamel wear and dentime wear, respectively. Tooth wear lesions were symmetrically distributed in the dental arches. Teeth in the upper arch were more affected by enamel wear than teeth in the lower arch while dentime wear was more in the lower arch than in the upper arch.